SAPIENS A BRIEF HISTORY OF HUMANKIND: STORY ABOUT HUMAN EVOLUTION AND CHALLENGES AHEAD - V. L. Sinta Herindrasti (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
Yuval Noah Harari is a history professor of Israeli births who has written three books of best-Seller namely sapiens A Brief History of Humankind (2011), the future Homo Deus of Mankind (2015) and 21 Lessons for the 21st century (2018). If the first book tells of human life in the past, the second book is exploring the human being of the future, and then the last book sees human nature now. Sapiens first published in Hebrew in 2011 and later published in English in 2014.